Caregiver determinants and capacity for participation in constraint-induced movement therapy - Moore, Hunter G.; Ayala, Amy; Aravamuthan, Bhooma R.; Smith, Alyssa E.; Ramey, Sharon L.; Hoyt, Catherine R. (Frontiers in Pediatrics, 2025)
AimHemiplegic cerebral palsy affects 1 in every 1,100 children, making it the most common pediatric motor disability. Constraint-Induced Movement Therapy (CIMT) is an evidence-based intervention that significantly improves upper extremity function when implemented with high fidelity. Despite its effectiveness, CIMT's intensive nature—requiring daily therapy for up to twenty days—limits its availability. This study examined caregivers’ perspectives on implementing and adapting home-based CIMT to identify practical solutions for improving intervention accessibility.MethodCaregivers of a child who has a diagnosis associated with upper extremity motor impairment consistent with cerebral palsy were recruited from the Cerebral Palsy Center at the St. Louis Children's Hospital. Caregivers completed a semi-structured interview to share their CIMT experiences, as well as their ideas and opinions related to modified versions of CIMT. All interviews were coded and analyzed for themes using descriptive analysis.ResultsTwelve interviews were conducted and revealed that caregivers would be interested in CIMT with an at-home model. Those who had experience with CIMT stated they found meaningful results from their participation in CIMT. Caregivers communicated potential challenges such as their child remaining engaged in at-home therapy, caregiver confidence in implementing the therapy, and the time required for implementing caregiver-led, home-based CIMT.InterpretationStudy findings identified that caregivers see value in a modified, at-home CIMT program. Developing a modified version of CIMT is needed to increase access to this beneficial intervention.